Pengembangan Aplikasi Android Penghimpun Data Ekonomi Nasional Berbasis Crowdsourcing - Azimi, Indra; Azimi, Aulia (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2016)
The right decision in national economy sector can only be obtained with excellent national economic data quality. Unfortunately, the collection process of true, accurate and complete national data is still expensive and time-consuming. Therefore, this study offers crowdsourcing as an alternative method towards the collection process of national data with low cost and dynamic. With case study basic commodity prices data collection nationwide, this method proved to empower the public as the owner of the data on self-reported commodities price in their region through an Android application, available for free on Google Play Store. This study was conducted for a year starting from January 2 to December 31, 2015. At the end of the study period, there were 7,442 people who have participated actively with an even distribution in all provinces in Indonesia. The amount of new user is 34 people per day with data entry is more than 400 data per day, and continues to increase.
Keywords: Android; crowdsourcing; pengumpulan data; data ekonomi nasional